Initiation of Post-Primary Tuberculosis of the Lungs: Exploring the Secret Role of Bone Marrow Derived Stem Cells - Pathak, Lekhika; Das, Bikul (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis (Mtb), the causative organism of pulmonary tuberculosis (PTB) now infects more than half of the world population. The efficient transmission strategy of the pathogen includes first remaining dormant inside the infected host, next undergoing reactivation to cause post-primary tuberculosis of the lungs (PPTBL) and then transmit via aerosol to the community. In this review, we are exploring recent findings on the role of bone marrow (BM) stem cell niche in Mtb dormancy and reactivation that may underlie the mechanisms of PPTBL development. We suggest that pathogen’s interaction with the stem cell niche may be relevant in potential inflammation induced PPTBL reactivation, which need significant research attention for the future development of novel preventive and therapeutic strategies for PPTBL, especially in a post COVID-19 pandemic world. Finally, we put forward potential animal models to study the stem cell basis of Mtb dormancy and reactivation.